Spillovers of U.S. unconventional monetary policy to emerging markets: The role of capital flows - Pablo Anaya; Michael Hachula; Christian Offermanns (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2015)
A growing literature stresses the importance of the 'global financial cycle', a common global movement in asset prices and credit conditions, for emerging market economies (EMEs). It is argued that one of the key drivers of this global cycle is monetary policy in the U.S., which is transmitted through international capital flows. In this paper, we add to this discussion and investigate empirically whether U.S. unconventional monetary policy (UMP) between 2008 and 2014 is related to financial conditions in EMEs, and, whether it is transmitted through portfolio flows. We find that a U.S. UMP shock significantly increases portfolio flows from the U.S. to EMEs for almost two quarters. The rise in inflows is accompanied by a persistent increase in several real and financial variables in EMEs. Moreover, we find that, on average, EMEs reacted with an easing of their own monetary policy stance in response to an expansionary U.S. shock.
Keywords: C54; E52; F42; 330; unconventional monetary policy; International capital flows; global financial cycle; global VAR; trilemma vs. dilemma